Uncommon presentation of left main congenital coronary aneurysm: a rare case report - Peng Xu; Shili Zhong; Hui Tan (Frontiers in Cardiovascular Medicine, 2024)
Coronary aneurysm, a dilated segment of the coronary artery, is a rare condition with a prevalence ranging from 0.02% to 0.2%. According to the current literature, reports of large aneurysms in the left main artery are extremely rare. We present a case of a 43-year-old male patient presenting with cough, wheezing, and dyspnea after a cold. Initial examinations suggested viral myocarditis, but further evaluation revealed a giant aneurysm in the left main coronary artery. Due to the high surgical risk, conservative treatment was chosen. Follow-up assessments showed no significant changes in the coronary aneurysm, with slight improvement in dyspnea. This rare case of a left main congenital coronary aneurysm suggests that treatment should consider the patient's overall condition, thrombosis presence, suitability for anticoagulant therapy, and aneurysm location and size.